The Influence of Brand Image and Price Perception on Consumer Purchase Decisions for New Balance Shoes in Sidoarjo - Cahyantoro, Herlangga Turna; Zawawi, Zawawi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In this research we take the phenomenon that exists on the Hybeast brand ranking website where New Balance occupies the top position and, in this research, we take the phenomenon where New Balance is included in the Top Brand Index (TBI). This phenomenon makes several individuals sell fake shoes or KW New Balance brand so New Balance in the Google Shopping Trend data has the lowest graph for the Sidoarjo area. This research was conducted to determine the influence of brand image and price perception on consumer purchase decisions for New Balance shoes in Sidoarjo. This research uses quantitative methods. The population of this study are people who have bought New Balance shoes and live in Sidoarjo with a sample of 110 respondents. Sampling used a purposive sampling method with test equipment using Partial Least Square (PLS). Making questionnaires using Google Forms and distributing them via social media. From the results obtained, statistical calculations show that brand image and price perception have a significant and positive influence on the decision to purchase New Balance shoes in Sidoarjo.